Peripartum Antibiotics Exposure and the Risk of Autoimmune and Autism Disorders in the Offspring - Almasri, Jehad; Barazi, Ahmed; King, Katherine S.; Walther-Antonio, Marina R. S.; Wang, Zhen; Murad, Mohammad H.; Murray, Joseph A.; Absah, Imad (Avicenna Journal of Medicine, 2021)
Background As the use of antibiotics during the peripartum period increases, the incidence of autoimmune disorders and autism spectrum disorders (ASDs) is also increasing. In this study, we aim to assess if antibiotic exposure during the peripartum period affects the incidence of autoimmune diseases and ASD in the offspring.Methods We identified children (< 18 years of age) born in Olmsted County from January 1, 2003 through December 31, 2012. Offspring with celiac disease (CD), inflammatory bowel disease (IBD), or ASD diagnoses were matched to two controls on birth date, index date, mother’s age at delivery, and sex. Data from the mother’s medical records were retrieved to determine peripartum antibiotics use.Results A total of 242 cases and 484 matched controls were included in this study. Median age at the last follow-up was 11.3 years (range: 0.5–14.9), 73% were males in both groups. Odds of CD diagnosis was not statistically different between vaginal delivery with antibiotics compared with vaginal delivery with no antibiotics (odds ratio [OR] = 0.76, 95% confidence interval [CI]: 0.32–1.85), similarly in IBD (OR = 2.41, 95% CI: 0.53–10.98) and ASD (OR = 1.00, 95% CI:0.55–1.79). Preeclampsia or eclampsia was associated with offspring CD (OR = 3.20, 95% CI: 1.05–9.78). Smoking history and diabetes mellitus were associated with offspring ASD (OR = 1.84, 95% CI: 1.22–2.77 and OR = 2.01, 95% CI: 1.03–3.91, respectively).Conclusion In this cohort, we found no statistically significant association between peripartum antibiotics exposure and the development of CD, IBD, or ASD.
Keywords: antibiotics exposure in pregnancy; autism; autoimmune disease; microbiome